The Effect Of Class-Wide Discussion Method On Students’ Conception Of Right Triangles (Journal of Namibian Studies : History Politics Culture, 2022)
The main purpose of the study is to determine the effect of the Class-wide Discussion Method (CWD) on students' level of conception on Right Triangles. The study involved one intact class which consists of twenty-four students of STI College -Paranaque during the first semester of school year 2010-2011. The instruments used in the study were researcher-made two-tier concept test administered in the pretest and the posttest, concept test for drills and exercises which were given during the Class-wide Discussion Method, questionnaire on the students' perception on the use of class-wide discussion method and the interview guide. The data gathered were interpreted quantitatively and qualitatively. This research study sought to answer the following specific problems: 1. What is the students' level of conception of right triangles before and after the class is taught using the Class-wide Discussion method? 2. What is the level of conception in each category of right triangle before and after the use of Class-wide Discussion method? 3. Are there differences on the students' level of conception of right triangles before and after the class is taught using the Class-wide Discussion method? 4. What is the students' perception on the use of the Class-wide Discussion method in solving right triangles? The effect of the Class-wide Discussion Method was determined by comparing the students' pretest and posttest scores in the Concept Test. Based on the result of the pretest and posttest, majority of the students' level of conception improve after the implementation of the Class-wide Discussion Method. As regards to students' views on the use of Class-wide Discussion method, students found the lessons interesting and enjoyable that eluded boredom. It was concluded that the use of Class-wide Discussion Method is enjoyable, helped students develop positive attitude towards mathematics, and enhanced students' conception on right triangles.